Physicochemical Factors Influencing . Contamination in Kathmandu Valley Ponds: Public Health and Environmental Implications - Niteesh Pokharel; Prajina Neupane; Ayushma Karki; Reshma Thapa; Surendra K. Pradhan (Environmental Health Insights)
Ponds in Kathmandu Valley reflect its rich history with water resources, but increasing pollution threatens public health and the environment. This study aimed to assess the physicochemical and microbial quality of pond water and further analyze the factors influencing E. coli contamination. In 2023, water samples from 27 out of a total of 35 ponds were examined for physicochemical parameters (temperature, pH, TSS, turbidity, iron (Fe 2+ ), nitrite (NO 2 − ), phosphate (PO 4 3− ), ammonia (NH 3 ), DO, BOD, and COD) and microbial parameters (total coliforms and E. coli ). Results revealed that all ponds exceeded WHO limits for TSS and turbidity for drinking water. Furthermore 67% surpassed the iron limit, while 96% exceeded USEPA’s BOD and COD levels for supporting aquatic life. Coliforms were present in all ponds, with E. coli detected in 67%, indicating the water was unfit for drinking under EU guidelines. Logistic regression revealed a significant association of COD and temperature ( P -values 0.001 and 0.023 respectively) with E. coli presence. A 3D visualization of the data further supports the association and illustrates these relationships, COD having a greater impact. These findings underscore public health risks and environmental concerns, urging sewage and runoff management and recommending expanded seasonal studies to establish comprehensive water quality guidelines.